2014
DOI: 10.18632/oncotarget.1993
|View full text |Cite
|
Sign up to set email alerts
|

MACC1 promotes carcinogenesis of colorectal cancer via β-catenin signaling pathway

Abstract: Here we confirmed that metastasis-associated in colon cancer 1 (MACC1) and β-catenin expression were higher in colorectal cancer (CRC) cells and tissues than those in normal colonic epithelial cell line and adjacent non-tumour colorectal mucosa (ANM) tissues, respectively. MACC1 expression was significantly related to histological differentiation (p<0.001), UICC stage (p=0.029), T classification (p=0.017), and N classification (p=0.023). Cox regression analysis demonstrated that high MACC1/abnormal β-catenin e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(57 citation statements)
references
References 20 publications
(28 reference statements)
3
54
0
Order By: Relevance
“…Recently, various studies have revealed that MACC1-induced tumorigenesis is closely correlated with hepatocyte growth factor (HGF)/ c-MET signaling pathway activation (6,10) leading to enhanced cell motility, invasion and metastasis (11). Furthermore, MACC1 could increase vimentin and suppress E-cadherin in colon cancer cells, but its silencing reversed these changes (12). To our knowledge, there is no report on its role regulating cell metastasis, as well as the underlying mechanism in carcinogenesis of malignant melanoma in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, various studies have revealed that MACC1-induced tumorigenesis is closely correlated with hepatocyte growth factor (HGF)/ c-MET signaling pathway activation (6,10) leading to enhanced cell motility, invasion and metastasis (11). Furthermore, MACC1 could increase vimentin and suppress E-cadherin in colon cancer cells, but its silencing reversed these changes (12). To our knowledge, there is no report on its role regulating cell metastasis, as well as the underlying mechanism in carcinogenesis of malignant melanoma in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…The following antibodies were used: β‐catenin, DKK3, cyclin D1, c‐Myc (Santa Cruz Biotech) 18, E‐Cadherin (Epitomics Inc.), vimentin, cleaved caspase‐3, cleaved caspase‐9, cleaved caspase‐7, cleaved PARP, E‐cadherin, vimentin, N‐Cadherin, Histone 1 (Cell Signaling Technology, Danvers, MA, USA) 19, β‐actin (Sigma‐Aldrich) 20, survivin, OCT4 and CD133 (Santa Cruz Biotech) 21, Glyceraldehyde 3‐phosphate dehydrogenase (Abcam) 22.…”
Section: Methodsmentioning
confidence: 99%
“…For various cancer cell lines, MACC1 has proven to induce proliferation and inhibit apoptosis [65,66]. Furthermore, several studies have revealed MACC1 to induce EMT by increasing the mesenchymal phenotype markers vimentin and CD44 and suppressing the epithelial phenotype markers E-cadherin and α-catenin [66][67][68].…”
Section: Metastasis Enhancer: Macc1mentioning
confidence: 99%
“…Furthermore, several studies have revealed MACC1 to induce EMT by increasing the mesenchymal phenotype markers vimentin and CD44 and suppressing the epithelial phenotype markers E-cadherin and α-catenin [66][67][68]. Recently, Wang et al [69] showed that MACC1 upregulates Twist-1/-2, a key EMT switch transcriptional regulator.…”
Section: Metastasis Enhancer: Macc1mentioning
confidence: 99%